Internal Migration, Remittances and Welfare Impacts: A Case Study in Dormaa Municipality, Ghana - Collins Yeboah (African Human Mobility Review, 2021)
Though international migration and its related remittance flows have attracted considerable attention in recent years, internal migration has been the focus of academic and policy discourse for a much longer period. Studies have shown that both internal and intra-regional migration are far more significant in terms of the numbers of people involved and the quantum of remittances involved than international migration. However, despite increasing internal migration with its associated remittances, their linkages with welfare impacts are complex and mixed. As such, the actual welfare impacts of this phenomenon have been a source of debate in the literature. Using mixed methods, this paper examines the relationship between internal migration, remittances and welfare impacts in Dormaa Municipality in Ghana. The study draws upon 202 migrant households on a sample of 358 households screened. The study investigates migration patterns and remittance flows, uses and impacts among migrant households in the municipality. The study suggests that many of the migrants moved to another town or village in Ghana for work-related reasons, notably job transfers, work or to seek work/better work. The study also shows that there have been substantial inflows of migrant remittances to households in Dormaa Municipality. These remittances have contributed significantly to improving migrant household’s access to health services and education, and have also become an important source of income for consumption smoothing. The study recommends that government should make efforts to monitor remittance flows in Ghana and also increase awareness about the importance of remittances for both national and household economies. Further, there is the need to scale up education on social attitudes and discourses about internal migration and policy initiatives in Ghana.